A Study on the Effects of the VALORANT eSports League in the Korean Video Game Market: Focusing on the Korean Internet Café Market Share (aSSIST Business Review, 2026)
This study explores the relationship between Valorant eSports league viewership and the market share of PC Cafés in South Korea, examining the theoretical implications of how digital platform-based eSports consumption may translate into actual offline gameplay. Given the distinctive ecosystem formed by PC Cafés and eSports in Korea, this research investigates whether high viewership of the Valorant eSports League potentially drives tangible player engagement, specifically reflected in PC Café usage. The study employs publicly accessible data, including daily viewership statistics from the official Valorant Champions Tour YouTube channel and PC Café market share rates as indicators of offline gameplay participation. Through data preprocessing, descriptive statistics, and regression analysis, the research positions Valorant eSports viewership as a lens to discuss the interplay between online engagement and offline gaming. Findings suggest that online platform engagement plays a central role in prompting players to transition from spectatorship to actual PC Café visits, underscoring the need for comprehensive strategies integrating eSports broadcasting schedules, content quality, and promotional efforts.
Keywords: Valorant; eSports; PC Café; Digital Engagement; eSports Marketing